Takhrij and Syarah Hadith of Cheymistry: Siwak for Oral and Dental Health - Siti Amelia Nurazizah; Wikhdatun Khasanah; Usep Dedi Rostandi; Tamami Tamami; Citra Fitriani K (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this research is to discuss the hadith of the Prophet Muhammad. about the content of miswak for oral health. This research method is qualitative through the takhrij and sharah hadith approaches with chemical analysis. The results and discussion of this study is proven that siwak has a very beneficial content for oral health. This research concludes that the use of siwak has been recommended by the Prophet Muhammad. based on takhrij and syarah hadith. This study recommends developing the benefits of miswak for oral health through chemistry.